The pursuit of knowledge : speeches and papers of Richard C. Atkinson - Atkinson, Richard C. (University of California Press, 2007)
Reveals the innovative approaches that deliberately shaped UC's role in the changing California. This title tells the story of the national controversy over the SAT and Atkinson's successful challenge to the dominance of the 75 year old college entrance examination. It highlights other issues with national significance.